Brain-wide topographic coordination of rotating waves - Zhiwen Ye; Alexander E. Ladd; Nancy MacKenzie; Ljuvica Kolich; Anna J. Li; Daniel Birman; Matthew S. Bull; Tanya L. Daigle; Bosiljka Tasic; Hongkui Zeng; Nicholas A. Steinmetz (Science, 2026)
Patterns of brain activity moving in waves occur across brain regions and species, yet their spatial organization, anatomical basis, and brain-wide distribution remain unclear. Using cortex-wide imaging and electrophysiology in awake mice, we revealed a prominent wave motif across spatial scales. Waves frequently formed rotational patterns centered on somatosensory cortex and sweeping across somatotopic maps. Axonal architecture within sensory cortex exhibited a matching circular arrangement. Rotating waves were mirrored between hemispheres and between sensory and motor cortex and were coordinated with subcortical spiking. Bilaterally cutting the circular circuitry diminished rotating waves. Rotating waves were modulated across behavioral states, evoked by sensory inputs, and recruited during correct visuomotor performance. These results establish that rotating waves are sculpted by axonal architecture across diverse brain systems and behavioral contexts.